Dampak Topografi Sulit dan Rendahnya Persebaran Penduduk Terhadap Ketersediaan Pelayanan Publik di Papua - Sarjito, Aris (Jurnal Publisitas, 2024)
This qualitative research investigates the impact of difficult topography and low population distribution on the availability and accessibility of public services in Papua. Drawing on secondary data sources, including academic articles and government reports, the study examines the challenges posed by Papua's rugged terrain and sparse population distribution to the provision of essential services such as healthcare, education, and infrastructure. The research aims to identify the implications of these challenges on public service quality in remote rural areas and explore interventions and strategies for enhancing service delivery. Findings reveal that difficult topography and low population distribution significantly hinder the availability and accessibility of public services in Papua. Remote rural areas experience disparities in service provision due to inadequate infrastructure, staffing shortages, and limited resources. These challenges lead to substandard service quality and compromised well-being among residents. However, interventions such as infrastructure improvements, capacity building, and community engagement show promise for addressing these challenges and promoting equitable development across the region.